Measurement of differential cross-sections in tt[bar] and tt[bar]+jets production in the lepton+jets final state in pp collisions at √s = 13 TeV using 140 fb−1 of ATLAS data - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Journal of high energy physics, 2024)
Differential cross-sections for top-quark pair production, inclusively and in association with jets, are measured in pp collisions at a centre-of-mass energy of 13 TeV with the ATLAS detector at the LHC using an integrated luminosity of 140 fb−1. The events are selected with one charged lepton (electron or muon) and at least four jets. The differential cross-sections are presented at particle level as functions of several jet observables, including angular correlations, jet transverse momenta and invariant masses of the jets in the final state, which characterise the kinematics and dynamics of the top-antitop system and the hard QCD radiation in the system with associated jets. The typical precision is 5%-15% for the absolute differential cross-sections and 2%-4% for the normalised differential cross-sections. Next-to-leading-order and next-to-next-to-leading-order QCD predictions are found to provide an adequate description of the rate and shape of the jet-angular observables. The description of the transverse momentum and invariant mass observables is improved when next-to-next-to-leading-order QCD corrections are included.
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [sehr viele weitere Personen]
Gesehen am 10.09.2025
Im Titel steht jeweils der 2. Buchstabe "t" mit einem Oberstrich
Im Titel ist der Ausdruck "-1" hochgestellt